Enhanced microwave absorbing properties of PANI/CoFe2O4/PVDF composite. Issue 102 (24th October 2016) - Yang, Haibo; Han, Ning; Lin, Ying; Zhang, Ge; Wang, Lei
Abstract : Polyaniline/CoFe2 O4 /polyvinylidene fluoride (PANI/CoFe2 O4 /PVDF) composites were synthesized by an in situ polymerization method. Abstract : Polyaniline/CoFe2 O4 /polyvinylidene fluoride (PANI/CoFe2 O4 /PVDF) composites were synthesized by an in situ polymerization method. The electromagnetic data demonstrate that the PANI/CoFe2 O4 /PVDF composite exhibit an excellent microwave absorption in the range of 2.0–18.0 GHz. The maximum reflection loss (RL) value can reach −57.7 dB at 7.6 GHz with a thickness of 4 mm and the absorption bandwidth with the RL below −10 dB is up to 3.4 GHz (from 6.5 to 9.9 GHz), which indicates that the microwave absorbing properties of the PANI/CoFe2 O4 composite can be enhanced by the introduction of PVDF and the PANI/CoFe2 O4 /PVDF composite has potential applications for high-efficient microwave absorbers.